2013
DOI: 10.1111/cyt.12091
|View full text |Cite
|
Sign up to set email alerts
|

The Bethesda system for reporting thyroid cytopathology: an institutional experience of the outcome of indeterminate categories

Abstract: The Bethesda system categorizes thyroid FNAs with increasing risk of malignancy as advocated. However, our findings suggest that the risk of malignancy for AUS/FLUS might be higher than estimated. Particularly, AUS/FLUS cases with focal features suggestive of PTC seem to be associated with a much higher risk of malignancy than other patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
64
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 24 publications
12
64
3
1
Order By: Relevance
“…Others do not support such observations [13][14]. In our material FLUS-O diagnoses were rarely formulated (2.5% of all FLUS), and only six nodules were verified with histopathological examination that revealed one cancer (16.7%).…”
Section: Prace Oryginalnecontrasting
confidence: 64%
See 2 more Smart Citations
“…Others do not support such observations [13][14]. In our material FLUS-O diagnoses were rarely formulated (2.5% of all FLUS), and only six nodules were verified with histopathological examination that revealed one cancer (16.7%).…”
Section: Prace Oryginalnecontrasting
confidence: 64%
“…As a consequence of the above-mentioned factors the risk of malignancy in FLUS nodules as assessed on the basis of postoperative histopathological examination ranges from 4% up to as much as 50% [12,[22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41], so it exceeds by several times the values suggested by NCI recommendations. Many authors indicate that the final malignancy results were observed several times more frequently in AUS than in FLUS [7][8][9][10][11][12][13][14]. In our material, in 1 of 3 cases of FLUS with features of nuclear atypia a papillary cancer was found in postoperative examination.…”
Section: Prace Oryginalnementioning
confidence: 41%
See 1 more Smart Citation
“…A high malignancy rate may be the result of many factors, including heterogeneity of AUS, or differences in interpretation of the cytological results by pathologists. [9] In our study, papillary carcinoma was the most frequently seen malignancy. Previous studies have reported that incidence rate of papillary carcinoma and follicular carcinoma were similar and that the follicular variant of papillary carcinoma was the most frequently seen.…”
Section: Discussionmentioning
confidence: 50%
“…[7,8] There is a 5% to 15% risk of malignancy in these cases. [9] Since it is difficult to determine whether atypia detected in cytological examination is benign or malignant, other clinical characteristics should be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%